Normal Variants of the Circle of Willis in patients undergoing CT Angiography - Prasad, V Natraj; Chhetri, Pramod Kumar; Paudel, Arun (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: The Circle of Willis represents the important anastomotic cerebral vessels at the base of the brain. Variation in the Circle of Willis is common. A complete or normal Circle of Willis varies widely in the literature. As no prior data on the variations of Circle of Willis is available on Nepalese population, this study was undertaken in patients undergoing CT Angiography. Materials & Methods: During the period July 2016 till Dec 2016, 65 patients who were referred for brain CT Angiography (Toshiba Aquilion Prime 160 slice Multi Detector CT scanner) from medicine, neurology and neuro-surgery were included in the study. CT scans were taken from the base of skull to the vertex. In addition to the axial source data, post-processed multiplanar reformatted (MPR), maximum-intensity projection (MIP), and 3D volume-rendering (VR) images were evaluated. Results: Of the 65 patients who underwent CT Angiography a normal or complete Circle of Willis was seen in only 35.4 % (23 patients). The most common variant of the Circle of Willis was a hypoplastic Pcom seen in 26.2 % (17 patients). This was followed by fetal origin of PCA seen in 13.8 % (9 patients). An absent Pcom and hypoplastic / absent Acom was in 12.3 % each (8 patients each). Conclusion: Variation in the Circle of Willis is common. Variations in the posterior portion of the Circle of Willis are more common than the anterior portion.